Smart street light / Anis Syahirah Riduan & Nursalmi Sapari - Riduan, Anis Syahirah; Sapari, Nursalmi (2015)
Our project title is Smart Street Light. Nowadays, people will find many way to save up the usage of energy to avoid the completely loss of natural sources. People also want to reduce light pollution that happened at night when the street light that light up even when there is no cars that pass by the road or highways. The Smart Street Light is an improved process from the previous system of street light. The operation of the light will on and off automatically will tell the user about the present of the other user, so they will beware each other and drive save. When the users pass by the road the street light will tum off automatically, so this new operation will reduced the wasteful usage of energy and the light pollution that produced unnecessary heat also will reduced.